Supported bifunctional thioureas as recoverable and reusable catalysts for enantioselective nitro-Michael reactions - Andrés, José M.; Ceballos, Miriam; Maestro, Alicia; Sanz, Isabel; Pedrosa, Rafael (Beilstein Journal of Organic Chemistry, 2016)
The catalytic activity of different supported bifunctional thioureas on sulfonylpolystyrene resins has been studied in the nitro-Michael addition of different nucleophiles to trans-β-nitrostyrene derivatives. The activity of the catalysts depends on the length of the tether linking the chiral thiourea to the polymer. The best results were obtained with the thiourea derived from (L)-valine and 1,6-hexanediamine. The catalysts can be used in only 2 mol % loading, and reused for at least four cycles in neat conditions. The ball milling promoted additions also worked very well.
Keywords: bifunctional organocatalysts; organocatalysis; stereoselective nitro-Michael addition; supported catalysts; thioureas